2011
DOI: 10.1089/sur.2010.039
|View full text |Cite
|
Sign up to set email alerts
|

Does Delaying Early Intravenous Fat Emulsion during Parenteral Nutrition Reduce Infections during Critical Illness?

Abstract: Withholding IVFE therapy during the first seven to ten days of PN did not influence infectious complications or the mortality rate in SICU patients. The benefits of delaying IVFE therefore may not be generalizable to all critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 28 publications
1
27
2
Order By: Relevance
“…While the recommendation to leave off fat the first week is based primarily on the Battistella study, 268 it is important to note serious criticisms of that trial. The study was completed 20 years ago, and the results have not been replicated 266 , 271 , 272 . The caloric goals were based on nonprotein calories (not total calories) such that the total calories delivered were greater than what was stated in the paper.…”
Section: H When Indicated Maximize Efficacy Of Pnmentioning
confidence: 99%
“…While the recommendation to leave off fat the first week is based primarily on the Battistella study, 268 it is important to note serious criticisms of that trial. The study was completed 20 years ago, and the results have not been replicated 266 , 271 , 272 . The caloric goals were based on nonprotein calories (not total calories) such that the total calories delivered were greater than what was stated in the paper.…”
Section: H When Indicated Maximize Efficacy Of Pnmentioning
confidence: 99%
“…No differences in infections, LOS, mechanical ventilation, or death were observed. The investigators concluded from this retrospective review that withholding SO‐based ILE did not improve infectious complications or clinical outcomes …”
Section: Studies Investigating Early Withholding Of So‐based Ilementioning
confidence: 94%
“…There was a single‐center retrospective trial evaluating delayed SO‐based ILE delivery . Based on the 2009 ASPEN/SCCM Guidelines for the provision and assessment of nutrition support therapy in the adult critically ill patients, the institution where the investigators practiced implemented a change in protocol by delaying SO‐based ILE within the first 7 days of hospitalization.…”
Section: Studies Investigating Early Withholding Of So‐based Ilementioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study of delayed intravenous lipid emulsion in adult surgical ICU patients demonstrated no change in infectious complications or mortality when compared with isocaloric PN containing lipid emulsions. 65 Increasing dextrose in PN to meet full calorie needs when lipid emulsion is withheld or limited may exceed limits for dextrose oxidation and exacerbate stress hyperglycemia.…”
Section: Nutrition Support Considerations For Glycemic Controlmentioning
confidence: 99%